2007
DOI: 10.1111/j.1399-3054.2006.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of turnip crinkle virus infection on the structure and function of mitochondria and expression of stress proteins in turnips

Abstract: Lee, Kit W.; Morris, Thomas Jack; and Elthon, Thomas, "Effects of turnip crinkle virus infection on the structure and function of mitochondria and expression of stress proteins in turnips" (2007). Virology Papers. 121.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Interestingly, close inspection of these p36-containing globular structures at higher magnification revealed that they actually consisted of numerous torus or donut-shaped structures that contained myc-p36 or p36-myc and that enclosed spherical fluorescent structures containing matrix-localized E1β (refer to arrowheads in Figure 1 ). These toroidal structures also contained the endogenous mitochondrial outer membrane protein porin [ 24 ], as evidenced by the colocalization of p36-myc and porin (Figure 1 ). Taken together, these results indicate that p36 sorts to mitochondrial outer membranes in BY-2 cells and that the expression of this viral protein causes mitochondria to coalesce in perinuclear regions, in contrast to mitochondria in non-transformed cells that are distributed throughout the cytosol; refer to images of the immunostaining of endogenous mitochondrial porin and E1β in the non-transformed cells shown in the bottom row of Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, close inspection of these p36-containing globular structures at higher magnification revealed that they actually consisted of numerous torus or donut-shaped structures that contained myc-p36 or p36-myc and that enclosed spherical fluorescent structures containing matrix-localized E1β (refer to arrowheads in Figure 1 ). These toroidal structures also contained the endogenous mitochondrial outer membrane protein porin [ 24 ], as evidenced by the colocalization of p36-myc and porin (Figure 1 ). Taken together, these results indicate that p36 sorts to mitochondrial outer membranes in BY-2 cells and that the expression of this viral protein causes mitochondria to coalesce in perinuclear regions, in contrast to mitochondria in non-transformed cells that are distributed throughout the cytosol; refer to images of the immunostaining of endogenous mitochondrial porin and E1β in the non-transformed cells shown in the bottom row of Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Fixed and permeabilized cells were processed for immunofluorescence microscopy as described by Trelease et al [ 91 ]. Primary and dye-conjugated secondary antibodies and sources were as follows: mouse anti-myc antibodies in hybridoma medium (clone 9E10; Princeton University, Monoclonal Antibody Facility, Princeton, NJ, USA); mouse anti-CAT antibodies in hybridoma medium (provided by S. Subramani, University of California, San Diego); rabbit anti-cottonseed catalase IgGs [ 92 ]; mouse anti-maize porin [ 24 ]; rabbit anti-pea E1β [ 93 ]; mouse anti-α-tubulin (clone DM 1A) (Sigma-Aldrich Ltd.); rabbit anti-myc and mouse anti-HA (Bethyl Laboratories, Montgomery, TX, USA); rabbit anti-p36 antibodies were raised against a synthetic peptide corresponding to an identical amino acid sequence in both p36 and TBSV p33 (-VEPARELKGKDGEDLLTGSR-) (residues 218–237 in p36 and 184–203 in p33) (refer to the p33 and p36 sequence alignment shown in Figure 4A ) [ 25 ]; goat anti-mouse Alexa Fluor 488 IgGs (Cedar Lane Laboratories, Ontario, Canada); goat anti-rabbit rhodamine red-X IgGs (Jackson ImmunoResearch Laboratories, West Grove, PA, USA). Concanavalin A conjugated to Alexa 594 (Molecular probes, Eugene, OR) was added to BY-2 cells at a final concentration of 5 μg mL -1 during the final 20 min of incubation with secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…1, G and H). Turnip crinkle virus (TCV) replicates on the outer mitochondrial membrane (Russo and Martelli, 1982;Blake et al, 2007), whereas cucumber mosaic virus (CMV) is thought to replicate in the cytoplasm (Zitter and Murphy, 2009). Accumulation of neither TCV nor CMV was significantly different in DTT-or tunicamycin-treated Arabidopsis (Arabidopsis thaliana) plants as compared to the respective control plants (Fig.…”
Section: Smv Infection Is Associated With the Induction Of Uprassociamentioning
confidence: 99%
“…TCV CP accumulates primarily in the cytoplasm of TCV-infected cells where virion assembly takes place (Blake et al, 2007). Nevertheless, it was predicted to contain a putative nuclear localization signal (NLS) (Kang, 2012).…”
Section: Resultsmentioning
confidence: 99%